Implementasi Metode TOPSIS-CRITIC pada Pengembangan Sistem Pendukung Keputusan Pemilihan Varietas Tanaman Kopi Robusta Berdasarkan Kondisi Lingkungan - Dinda Rachma Ayu Mauliza (Fakultas Ilmu Komputer, 2026)
Robusta coffee is a plantation commodity that has dominated national production, accounting for 72,71% of total coffee production over the last decade. Jember Regency is one of the regions producing high-quality robusta coffee because it is dominated by highlands with fertile soil. However, farmers still choose robusta coffee varieties conventionally based on subjective considerations, resulting in suboptimal plant production and unstable crop yields. Therefore, this study aims to build a website-based Decision Support System (DSS) to assist farmers in Jember Regency in objectively determining robusta coffee varieties recommended by the Indonesian government, namely BP 920, BP 436, BP 409, BP 939, BP 42, BP 936, BP 308, BP 288, BP 534, BP 358, SA 203, and SA 237. The evaluation is conducted based on five environmental criteria: soil type, rainfall, temperature, environmental humidity, and altitude. The method used is a hybrid of Criteria Importance Through Inter Criteria Correlation (CRITIC) for objective criteria weighting and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for ranking the varieties. The system recommends BP 920 variety as the main priority, followed by BP 436, BP 409, and BP 939 to be planted simultaneously in polyclonal manner. The accuracy level of the system was tested using the Spearman Rank Correlation method by comparing the system’s ranking results with the expert’s rankings. The test results showed a correlation value of 0,7552. This value indicates that the system has a very high level of accuracy, making the developed system highly feasible to be used as a supportive tool for robusta coffee farmers in Jember.
Validasi dan Finalisasi oleh Taufik 29 Mei 2026
Keywords: Decision Support System; Robusta Coffee; TOPSIS; CRITIC; Spearman Rank Correlation